Clinical–Radiological Severity Mismatch Phenomenon: Patients with Severe Neurological Deficits Without Matching Infarction on Computed Tomographic Scan. Issue 1 (10th December 2012) - Qureshi, Adnan I.; Chaudhry, Saqib A.; Sivagnanam, Kamesh; Rodriguez, Gustavo J.; Suri, M. Fareed K.; Lakshminarayan, Kamakshi; Ezzeddine, Mustapha A.
<x xml:space="preserve">Abstract</x> ABSTRACT OBJECTIVE The objective was to determine the long‐term outcome of patients with severe persistent neurological deficits without a large infarction on computed tomographic (CT) scan. METHODS We analyzed the prospectively collected data as part of the randomized, placebo controlled trial in patients with ischemic stroke presenting within 3 hours of symptom onset. Volume of infarction was measured from CT scan acquired at 3 months. Favorable outcome defined by no significant or slight disability on a modified Rankin scale at 12 months. We determined the outcome of patients with National Institutes of Health Stroke Scale score (NIHSS score) ≥10 at 24 hours. RESULTS Of the 277 patients with NIHSS score ≥10 at 24 hours, 88 (32%) met the criteria of clinical–radiological severity mismatch. Compared with patients with NIHSS score ≥10 with infarct volume ≥20 cc, the patients with NIHSS score ≥10 and infarct volume <20 cc were older but there were no differences in the gender, race or vascular risk factors. Patients with clinical–radiological severity mismatch were more likely to have a favorable outcome at 12 months compared with those without mismatch (odd ratio 4.3, 95% confidence interval 1.5‐12.6, P= .0063) after adjusting for potential confounders. CONCLUSIONS We observed that approximately one‐fourth of patients with severe neurological deficits have clinical–radiological severity mismatch. Such patients appear to have a high rate of favorable outcomes at 1 year.